2010
DOI: 10.1542/peds.2009-0712
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure and Neurodevelopmental Disorders in Children Adopted From Eastern Europe

Abstract: Fetal alcohol spectrum disorders and neurodevelopmental disorders were common in this long-term follow-up study of children adopted from orphanages in eastern Europe. Maternal alcohol consumption during pregnancy has long-lasting adverse effects, causing structural, behavioral, and cognitive damage despite a radically improved environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
123
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 31 publications
9
123
0
8
Order By: Relevance
“…Extant reports about the association between prenatal risk and later indiscriminate behaviors are inconsistent, 4,29 and measurement of prenatal risk is fraught with challenges in children with an institutional history. 30 To date, there is limited evidence indicating an important role for prenatal factors in the genesis of indiscriminate behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Extant reports about the association between prenatal risk and later indiscriminate behaviors are inconsistent, 4,29 and measurement of prenatal risk is fraught with challenges in children with an institutional history. 30 To date, there is limited evidence indicating an important role for prenatal factors in the genesis of indiscriminate behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four articles (representing 33 studies) contained relevant data and were selected for data extraction. A schematic diagram of the search strategy is depicted in Fig 1. Data on the prevalence of FAS and/or FASD in child-care systems were available from only 8 countries, as follows: Brazil (1 study 40 ), Chile (2 studies 41,42 ) Canada (3 studies 4,43,44 ), Israel (1 study 45 ), Russia (10 studies 11,46-55 ), Spain (1 study 56 ), Sweden (3 studies [57][58][59] ), and the United States (USA; 11 studies [60][61][62][63][64][65][66][67][68][69][70] ). One study reported on the prevalence of FAS among preadoption children from Eastern Europe (Romania, Ukraine, Moldova).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The 2 countries with the highest reported prevalence of FAS among children and youth in child-care settings were Russia 54,55 and Sweden, 58 71 (preadoption children from Romania, Ukraine, Moldova) and the United States 62 (adoptees from China) had a reported prevalence for FAS of 0 per 1000. As with FAS, the 2 countries with the highest reported prevalence of FASD among children and youth in child-care settings were Russia 47 and Sweden, 58 397 per 1000 (orphanage) and 521 per 1000 (adoptees from Eastern Europe), respectively, and 40 per 1000 was reported for Israel 45 (foster care and preadoption children) and the United States 64,68 (adoptees from Eastern Europe).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations